\(\int\limits^2_1\frac{\ln\left(x+1\right)}{x^2}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

4 tháng 4 2016

\(\int\limits^2_1\frac{\ln\left(x+1\right)}{x^2}dx=-\frac{\ln\left(x+1\right)}{x^2}+\int\limits^2_1\frac{1}{x\left(x+1\right)}dx=\ln2-\frac{\ln3}{2}+\int\limits^2_1\left(\frac{1}{x}-\frac{1}{x+1}\right)dx\)

                   \(=\ln2-\frac{\ln3}{2}+\ln\left(\frac{x}{x+1}\right)|^2_1=\ln2-\frac{\ln3}{2}-\ln3=\frac{\ln2-3\ln3}{2}\)

27 tháng 4 2017

Hỏi đáp Toán

29 tháng 11 2019
https://i.imgur.com/Pe6vPSJ.jpg
AH
Akai Haruma
Giáo viên
12 tháng 7 2017

Câu a)

Đặt \(y=\sqrt{t}\Rightarrow I_1=\int ^{1}_{0}(y-1)^2\sqrt{y}dy=\int ^{1}_{0}(t^2-1)^2td(t^2)\)

\(\Leftrightarrow I_1=2\int^{1}_{0}(t^2-1)^2t^2dt=2\int ^{1}_{0}(t^6-2t^4+t^2)dt\)

\(=2\left.\begin{matrix} 1\\ 0\end{matrix}\right|\left ( \frac{t^7}{7}-\frac{2t^5}{5}+\frac{t^3}{3} \right )=\frac{16}{105}\)

b) Đặt \(u=\sqrt[3]{z-1}\Rightarrow z=u^3+1\Rightarrow I_2=\int ^{1}_{0}[(u^3+1)^2+1]u^2d(u^3+1)\)

\(\Leftrightarrow I_2=3\int ^{1}_{0}[(u^3+1)^2+1]u^4du=3\int ^{1}_{0}(u^{10}+2u^7+2u^4)du\)

\(=3\left.\begin{matrix} 1\\ 0\end{matrix}\right|\left ( \frac{x^{11}}{11}+\frac{x^8}{4}+\frac{2x^5}{5} \right )=\frac{489}{220}\)

AH
Akai Haruma
Giáo viên
12 tháng 7 2017

c) Ta có:

\(I_3=\int ^{e}_{1}\frac{\sqrt{4+5\ln x}}{x}dx=\int ^{e}_{1}\sqrt{4+5\ln x}d(\ln x)\)

Đặt \(\sqrt{4+5\ln x}=t\Rightarrow I_3=\int ^{3}_{2}td\left (\frac{t^2-4}{5}\right)=\frac{2}{5}\int ^{3}_{2}t^2dt=\frac{38}{15}\)

d)

Xét \(\int ^{\frac{\pi}{2}}_{0}\cos ^5xdx=\int ^{\frac{\pi}{2}}_{0}\cos ^4xd(\sin x)=\int ^{\frac{\pi}{2}}_{0}(1-\sin ^2x)^2d(\sin x)\)

\(=\int ^{1}_{0}(1-t^2)^2dt\)

Xét \(\int ^{\frac{\pi}{2}}_{0}\sin ^5xdx=-\int ^{\frac{\pi}{2}}_{0}\sin ^4xd(\cos x)=-\int ^{\frac{\pi}{2}}_{0}(1-\cos ^2x)^2d(\cos x)=\int ^{1}_{0}(1-t^2)^2dt\)

Do đó \(\int ^{\frac{\pi}{2}}_{0}(\cos ^5x-\sin ^5x)dx=0\)

e)

\(\int \cos ^3x\cos 3xdx=\int \cos 3x\left ( \frac{3\cos x+\cos 3x}{4} \right )dx=\frac{1}{4}\int \cos ^23xdx+\frac{3}{4}\int \cos x\cos 3xdx\)

\(=\frac{1}{8}\int (1+\cos 6x)dx+\frac{3}{8}\int (\cos 4x+\cos 2x)dx\)

\(=\frac{1}{8}\int (1+\cos 6x)dx+\frac{3}{8}\int (\cos 4x+\cos 2x)dx=\frac{x}{8}+\frac{\sin 6x}{48}+\frac{3\sin 4x}{32}+\frac{3\sin 2x}{16}\)

Suy ra \(\int ^{\pi}_{0}\cos ^3x\cos 3xdx=\frac{\pi}{8}\)

4 tháng 4 2016

Đặt \(u=\ln x\rightarrow du=\frac{dx}{x},dv=\int_1^2\frac{dx}{x^3}\rightarrow v=-\frac{1}{2x^2}\)

Do vậy : \(I=-\frac{1}{2x^2}\ln x|^2_1+\frac{1}{2}\int\limits^2_1\frac{dx}{x^3}=-\frac{\ln2}{8}-\frac{1}{4x^2}|^2_1=\frac{3-2\ln2}{16}\)

23 tháng 9 2017

E.Di chuyển

AH
Akai Haruma
Giáo viên
20 tháng 3 2017

Câu a)

\(I=\int ^{1}_{0}\frac{x(e^x+1)+1}{e^x+1}dx=\int ^{1}_{0}xdx+\int ^{1}_{0}\frac{dx}{e^x+1}\)

\(=\left.\begin{matrix} 1\\ 0\end{matrix}\right|\frac{x^2}{2}+\int ^{1}_{0}\frac{d(e^x)}{e^x(e^x+1)}=\frac{1}{2}+\left.\begin{matrix} 1\\ 0\end{matrix}\right|\ln\left | \frac{e^x}{e^x+1} \right |\)

\(\Leftrightarrow I=\frac{3}{2}+\ln 2-\ln (e+1)\)

Câu d)

\(I=\int ^{e}_{1}\ln(x+1)d(x)=\int ^{e}_{1}\ln (x+1)d(x+1)\)

Đặt \(\left\{\begin{matrix} u=\ln (x+1)\\ dv=d(x+1)\end{matrix}\right.\Rightarrow \left\{\begin{matrix} du=\frac{d(x+1)}{x+1}\\ v=x+1\end{matrix}\right.\)

\(\Rightarrow I=\left.\begin{matrix} e\\ 1\end{matrix}\right|(x+1)\ln (x+1)-\int ^{e}_{1}d(x+1)\)

\(=(e+1)\ln \left ( \frac{e+1}{e} \right )-2\ln \left (\frac{2}{e}\right )\)

AH
Akai Haruma
Giáo viên
20 tháng 3 2017

Câu b)

Đặt \(\tan \frac{x}{2}=t\). Ta có:

\(\left\{\begin{matrix} dt=d\left ( \tan \frac{x}{2} \right )=\frac{1}{2\cos ^2\frac{x}{2}}dx=\frac{t^2+1}{2}dx\rightarrow dx=\frac{2dt}{t^2+1}\\\ \cos x=\frac{1-t^2}{t^2+1}\end{matrix}\right.\)

\( I=\underbrace{\int ^{\frac{\pi}{2}}_{0}\frac{1}{1+\cos x}dx}_{A}+\underbrace{\int ^{\frac{\pi}{2}}_{0}\frac{d(\cos x)}{\cos x+1}}_{B}\)

\(B=\int ^{\frac{\pi}{2}}_{0}\frac{d(\cos x+1)}{\cos x+1}=\left.\begin{matrix} \frac{\pi}{2}\\ 0\end{matrix}\right|\ln |\cos x+1|=-\ln 2\)

\(A=\int ^{1}_{0}\frac{2dt}{(t^2+1)\frac{2}{t^2+1}}=\int ^{1}_{0}dt=1\)

\(\Rightarrow I=A+B=1-\ln 2\)

NV
29 tháng 3 2019

1/ \(\int\limits^e_1\left(x+\frac{1}{x}+\frac{1}{x^2}\right)dx=\left(\frac{x^2}{2}+lnx-\frac{1}{x}\right)|^e_1=\frac{e^2}{2}-\frac{1}{e}+\frac{3}{2}\)

2/ \(\int\limits^2_1\left(\sqrt{x}+1\right)\left(x-\sqrt{x}+1\right)dx=\int\limits^2_1\left(x\sqrt{x}+1\right)dx=\int\limits^2_1\left(x^{\frac{3}{2}}+1\right)dx\)

\(=\left(\frac{2}{5}.x^{\frac{5}{2}}+x\right)|^2_1=\frac{8\sqrt{2}-7}{5}\)

3/

\(\int\limits^2_1\frac{2x^3-4x+5}{x}dx=\int\limits^2_1\left(2x^2-4+\frac{5}{x}\right)dx=\left(\frac{2}{3}x^3-4x+5lnx\right)|^2_1=\frac{2}{3}+5ln2\)

4/ \(\int\limits^2_1x^2\left(3x-1\right)\frac{2}{x}dx=\int\limits^2_1\left(6x^2-2x\right)dx=\left(2x^3-x^2\right)|^2_1=11\)